Adjuvants for the construction anticancer vaccines based on chick embryonic proteins - Gregirchak, Natalia; Lych (Tkachenko), Inna (My University, 2014)
It was chosen potential excipients for the design of cancer vaccines and study their effects on the immune system in experimental animals with Lewis lung carcinoma.
Keywords: vaccine; вакцина; adjuvant; ад'ювант; кафедра біотехнології і мікробіології